The influence of organizational culture on the emergence of a blaming culture and its implications for workplace safety: A review article - Gilang Arya Ramadhan; Didik Mustakim; Achmad Jusuf Zulfikar (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
Organizational culture plays a fundamental role in shaping employee behavior, including how occupational safety and health (OSH) practices are implemented and sustained. A toxic organizational culture can give rise to a blaming culture, in which individuals are unfairly blamed for workplace accidents or incidents without addressing the underlying systemic causes. This review article aims to explore the connection between organizational culture, the emergence of blaming culture, and its implications for workplace safety. Using a narrative literature review methodology, the study analyzed 30 peer-reviewed articles published between 2018 and 2024, sourced from reputable databases such as Scopus, ScienceDirect, and Google Scholar. The review revealed that rigid organizational structures, top-down communication styles, and a strong focus on outcomes over processes often contribute to the formation of blaming cultures. Conversely, organizational cultures that encourage transparency, open communication, continuous learning from errors, and transformational leadership are more likely to foster a just culture, which that balances accountability with learning and supports proactive safety management. The article concludes that cultural transformation within organizations is essential for dismantling blame-oriented practices. Implementing supportive and inclusive cultural strategies can significantly enhance employee trust, encourage reporting of safety concerns, and ultimately create a safer and more resilient working environment.